Coprodução de autonomia na Atenção Primária à Saúde em Belo Horizonte-MG - Ana Clara Rocha Franco (2022)
Primary Health Care (PHC) has as one of its objectives the development of comprehensive care that impacts people's health and autonomy. Autonomy is the foundation and guideline of the da Política Nacional da Atenção Básica (2017) and the Política Nacional de Promoção da Saúde (2006). However, it is observed that the practices carried out within the scope of PHC are guided by the conduct of care based on a biomedical model, centered on a prescriptive logic. This study reflects on the way in which practices are offered at this level of care and the possibilities for these to be promoters of autonomous care. The concept of autonomy that guides this study considers the ability of subjects to understand and act on themselves and their dependency networks. In this sense, autonomy in PHC is understood as a co-production between workers and users, that is, a relational technology in health. From this, this study had the general objective of analyzing possible processes of co-production of autonomy in health practices in PHC in Belo Horizonte, and specific objectives: to analyze elements that workers and users associate with a care practice in PHC that expands the conditions users to think and intervene about their health; to analyze the limits and potential for the co-production of autonomy between workers and users in PHC. Open interviews were conducted with experts, workers and users. The thematic analysis of the data relied on triangulation of researchers. Workers and users associate self-care, accountability and bonding with autonomous elements. It is noteworthy that these elements operate in a prescriptive and individualizing logic, but there is a commitment of the subjects to promote meetings that co-produce autonomy through openness to dialogue, listening and choices, having the bond as a basis for the co-production of autonomy. For professionals, there are certain conditions that enable or make it impossible for users to reflect and act on their health. Structural and organizational difficulties are also identified in the Health Centers for the co-production of autonomy in PHC. It is concluded that, although PHC is a powerful space for the co-production of autonomy, it is necessary to encourage and sustain in-service training processes, such as Permanent Health Education, to expand the clinic and comprehensive care, stressing the prevailing prescriptive logic and performing an opening movement for the production of diverse and plural subjectivities.